Revisiting al-Ghazali’s Criticism on Scholastic Theology: An Examination of al-Munqidh Min al-Ḍalāl - Ali, Samaila; Muhammad, Habeeb (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
The debate surrounding Ilm al-Kalam represents one of the enduring discourses in the Islamic intellectual tradition. While some scholars view it as an essential tool for safeguarding the creed through rational inquiry, others criticize it for prioritizing reason over divine revelation. This study employs a qualitative approach to explore Al-Ghazali’s contributions to the development of Ilm al-Kalam and critically examines his later critiques as articulated in his autobiographical work al-Munqidh min al-Ḍalāl. The findings reveal that Al-Ghazali, a central figure within the Ash‘arite tradition, significantly shaped Islamic theological discourse through his extensive writings and intellectual influence. However, in the latter part of his life, he presented three major criticisms of Ilm al-Kalam: first, the rejection of rationality as a primary source of religious knowledge; second, a critique of theologians’ methods of refutation, which often lack independent reasoning; and third, their tendency toward taqlid (blind imitation). This study concludes that Al-Ghazali’s critiques reflect an epistemological anxiety over the limitations of reason in comprehending divine realities. Therefore, a balanced theological approach is needed—one that integrates rational reflection with the authority of revelation—to navigate the boundaries of Islamic theological thought more effectively.